2016
DOI: 10.1016/j.jneb.2016.03.011
|View full text |Cite
|
Sign up to set email alerts
|

Snacking Among US Children: Patterns Differ by Time of Day

Abstract: Snacking is an important contributor to energy and nutrients in children's diets, but foods and beverages selected vary by time of day and age. Modifying snacking choices, especially in the afternoon, could improve the nutritional quality of children's diets.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
55
1
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(62 citation statements)
references
References 28 publications
4
55
1
1
Order By: Relevance
“…In agreement with the US, Brazil and France (5,6,8), we observed that mid-afternoon snack consumption prevalence decreased with age. The number of food items consumed during a mid-afternoon snack occasion decreases with age; older children consume a unique food item, which is mainly fruit or sandwich.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…In agreement with the US, Brazil and France (5,6,8), we observed that mid-afternoon snack consumption prevalence decreased with age. The number of food items consumed during a mid-afternoon snack occasion decreases with age; older children consume a unique food item, which is mainly fruit or sandwich.…”
Section: Discussionsupporting
confidence: 89%
“…In Brazil, 97% of children between four and six and 78% of children older than ten report a mid-afternoon snack daily (6,7), and in France, where mid-afternoon snack is a traditional meal, the consumption increases up to 87% of children from nine to eleven years of age (8). These studies have also shown that the percentages of meal snack consumers differ between younger and older children (5,6), with decreasing number of snack meals among older children.…”
Section: Introductionmentioning
confidence: 93%
See 3 more Smart Citations